From research to policy and practice: evidence from Bangladesh - Nasreen, Hashima E (2018)
Policy makers in Bangladesh are looking for effective ways of using research evidence to support policy making and to build good practices in improving population health. However, effective translation has been slow and inconsistent across low-income countries particularly in Bangladesh, and such inconsistencies contribute ubstantially to the suboptimal population health. This briefing looks at some of the wider issues about the relationship between research and policy raised by the three development programs in Bangladesh, such as improving maternal, neonatal and child survival; impact of maternal perinatal depression on infant growth and development; and HIV/AIDS prevention and care. Partnership approach, behavior change and engagement of population, service providers and stakeholder organizations have been identified as key elements in translating research evidence into policy, practice and population health in these projects. The briefing also discusses some possibilities and problems in what is coming to be known as ‘Knowledge Transfer’ from research to policy and practice, and reviews developments aimed at improving knowledge transfer in population health.